Labour nationality and religion - Connolly, James (Dublin : New Books, 1973)
Bibliotheek François Vercammen
Being a discussion of the Lenten Discourses against socialism delivered by Father Kane, S.J. in Gardiner Street Church, Dublin, 1910
Engels
Brochure